PENGELOLAAN PERBATASAN KABUPATEN TIMOR TENGAH DAN UTARA PASCA LEPASNYA TIMOR-TIMUR DARI INDONESIA DALAM MENDUKUNG KEDAULATAN NKRI - Titiek Herawati; M. Sigit Saksono; Silitonga, Frangky; Sopiin; F. Leandro; M. Andre Nuralam R (PPM Sdirjianbang Akademi Militer, 2024)
Despite Indonesia's strategic position, serious operationalisation of cross-border governance has not been placed as a top priority. In fact, the ability of a good state management (governability) can be seen from how the border area is managed. In most cases in our country, border areas not only lack the attention of the central government, the purpose of this research study is to find out the management of the border area of North Central Timor district after the release of East Timor from Indonesia. The method we use is a qualitative method so that the author collects data by utilising existing facilities at Akmil, namely the Internet, Akmil library, informants namely Akmil personnel who have served in the border area of North East Timor. It was agreed by the two countries to seek the establishment of development that can be jointly utilised by the two countries and border communities regarding economic welfare, security education and defence.